Deformation, Permeability and Acoustic Emission Characteristics of Coal Masses under Mining-Induced Stress Paths - Yi Xue; Faning Dang; Zhengzheng Cao; Feng Du; Jie Ren; Xu Chang; Feng Gao (Energies, 2018)
The geomechanical and seepage evolution characteristics of coal masses during mining are the key factors that affect the drainage of coalbed methane and the safety of coal mining. Nevertheless, the influence of mining paths on coal seam permeability is rarely investigated given the complexity of mining-induced stress experiments. To study the effect of mining-induced stress on coal mining, the mechanical properties, acoustic emission characteristics and energy evolution of coal masses were experimentally evaluated through mining-induced stress experiments. Experimental results indicated that at peak intensity, the deviatoric stress and axial strain of coal samples under the stress path of protective coal-seam mining are lower than those of coal samples under the non-pillar stress path. The unloading ratio of confining pressure is large under a stress path of non-pillar mining, and the elastic energy, the absorbed energy, and the dissipated energy of coal mass are low during destruction. The effect of high confining pressure on AE events is pronounced under the non-pillar mining path. The overall b value under high confining pressure is smaller than that under low confining pressure, and AE events generally have high energy. The fracture structure of coal mass is complex, and the fractal size of coal is large under high unloading rates of confining pressure, which induce the increase of permeability after coal destruction.